Ribonucleic Acid Synthesis in Bacteria Treated with Toluene - Peterson, R. L. (J Bacteriol, 1971)
Escherichia coli and Bacillus megaterium rendered permeable to ribonucleoside triphosphates by toluene treatment retain the capacity to synthesize discrete ribonucleic acid species.